2002
DOI: 10.1128/jvi.76.14.6919-6928.2002
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Low- and Very-Low-Density Hepatitis C Virus RNA-Containing Particles

Abstract: The presence of hepatitis C virus (HCV) RNA-containing particles in the low-density fractions of plasma has been associated with high infectivity. However, the nature of circulating HCV particles and their association with immunoglobulins or lipoproteins as well as the characterization of cell entry have all been subject to conflicting reports. For a better analysis of HCV RNA-containing particles, we quantified HCV RNA in the low-density fractions of plasma corresponding to the very-low-density lipoprotein (V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
604
5
13

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 604 publications
(645 citation statements)
references
References 46 publications
23
604
5
13
Order By: Relevance
“…Quantification of HCV RNA in LVPs indicated that on average, 34% 6 26% of HCV RNA associated with low-density particles circulate as LVP immune complexes as reported. 4 ApoB was detected and quantified via ELISA in all but four patient samples (Fig. 1B).…”
Section: Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…Quantification of HCV RNA in LVPs indicated that on average, 34% 6 26% of HCV RNA associated with low-density particles circulate as LVP immune complexes as reported. 4 ApoB was detected and quantified via ELISA in all but four patient samples (Fig. 1B).…”
Section: Resultsmentioning
confidence: 92%
“…Electron microscopy of LVPs revealed large and single particles. 4 Similarly, in vitro-produced apoB and E1E2-positive, nucleocapsid-free particles have two-to three-fold larger diameters than E1E2-negative lipoproteins. 32 In addition, the higher molar ratios of neutral lipids on apoB in LVPs compared with TRLs indicates that such particles are not agglomerates of standard lipoproteins with LVPs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations